Hindu Society: An Interpretation - Irawati Karve (My University, 2019)
Deserving a wide reading, this critically acclaimed book unfurls the bewildering varieties of behavioural patterns and structure present in the Indian society and history of Indian society. In doing so the author presents a series of important theories related to the caste system based on her extensive field research and pertinent study in Sanskrit and allied literature from the time of Rig Veda.
Keywords: Kashmiri